Associação entre o exame clínico andrológico e testes de viabilidade espermática, integridade de acrossoma e fragmentação de cromatina para determinar a qualidade seminal de touros - Silva, Rogério Orfaly Addad da (2006)
Thirty six Nelore bulls with age between 30 and 120 months were used to evaluation of the seminal quality and the reproductive aptitude. The animals had been kept in extensive conditions, with feeding the grass, receiving mineral supplementation and serving a herd with 3,782 females of some categories (heifers and cows). Data enclosed measured of scrotal circumference and evaluation of the semen collected by eletroejaculation and evaluated the physical characteristics (volume, mass activity, motility, strong), morphologic (major, minor and total defects) and spermatic structure integrity (integrity of plasmatic membrane, acrosome and chromatin) in this period had been carried through that preceded three consecutive mating season (2003, 2004 and 2005). The data had been submitted analyze of variance, the averages compared for test SNK and the coefficient of correlation of Pearson was calculated using the SAS. The bulls presented scrotal circumference of 33.8 ± 2.8cm, 15.6 ± 8.5% of total spermatic defects, 40.1 ± 23.1% of gametes with normal membrane and acrosome and 8.8 ± 3.8% of fragmented chromatin. The relations between scrotal circumference, physical and morphologic characteristics, spermatic integrity and the reproductive performance of the herd had been low and not significant (P< 0.05). In sexually mature bulls the integrity of plasmatic membrane, acrosome and nuclear chromatin had not been the most frequent trouble of the spermatic morphology.